IgA anti-tissue transglutaminase as a diagnostic marker of gluten sensitive enteropathy. - Lock, R J (1999)
AIMS: To compare and contrast the sensitivity, specificity, and positive predictive values of IgA antibodies to guinea pig tissue transglutaminase (ELISA), endomysium, and reticulin (immunofluorescence), and gliadin (ELISA), and IgG antibodies to gliadin and tissue transglutaminase. METHODS: Sera from 27 newly diagnosed patients with coeliac disease, 65 biopsied gastrointestinal disease controls, and 50 consecutive blood donors were tested. All cases were adults. RESULTS: IgA anti-tissue transglutaminase showed a sensitivity of 85% (23/27 coeliac disease cases seropositive), specificity 97% (2/65 controls and one blood donor showing low titre positivity), and a positive predictive value of 92%. High titre anti-tissue transglutaminase was only seen in coeliac disease. Disease controls with mucosal damage unrelated to gluten enteropathy were IgA anti-tissue transglutaminase negative. Sensitivity, specificity, and positive predictive values for IgA anti-endomysial antibody (monkey oesophagus) were 100%, 100%, and 100%, respectively, and for IgA anti-gliadin, 93%, 95%, and 89%, respectively. CONCLUSIONS: Tissue transglutaminase is a major autoantigen in coeliac disease. IgA (but not IgG) anti-tissue transglutaminase, especially when in high titre, is closely associated with coeliac disease, but low titres may not be disease specific. In this small pilot study, the established IgA anti-endomysial assay was the superior test.